2017
DOI: 10.1186/s12879-017-2546-y
|View full text |Cite
|
Sign up to set email alerts
|

MSM HIV testing following an online testing intervention in China

Abstract: BackgroundScaling up HIV testing is the first step in the HIV treatment continuum which is important for controlling the HIV epidemic among men who have sex with men (MSM). Following an online HIV testing intervention among MSM, we aim to examine sociodemographic and spatial factors associated with HIV testing.MethodsWe conducted a secondary analysis on data from an online HIV testing intervention among MSM who had never-tested for HIV. The survey was distributed through online networks connected to all provin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 22 publications
2
11
2
Order By: Relevance
“…This rate is much lower than previously reported in Zambia [15], Botswana [16] and South Africa [17]. Whereas other studies showed that social stigma against HIV and STD [18], fear of testing [19] and lack of testing information [20] are main contributors of limiting HIV and syphilis testing, our study found that the most important barriers in this sample of Chinese heterosexual STD clinic attendees were a perceived low prevalence of HIV and syphilis. This highlights the importance of improving knowledge and awareness of HIV and syphilis infection among heterosexual STD clinic attendees on increasing the acceptance of PITC services.…”
Section: Discussioncontrasting
confidence: 88%
“…This rate is much lower than previously reported in Zambia [15], Botswana [16] and South Africa [17]. Whereas other studies showed that social stigma against HIV and STD [18], fear of testing [19] and lack of testing information [20] are main contributors of limiting HIV and syphilis testing, our study found that the most important barriers in this sample of Chinese heterosexual STD clinic attendees were a perceived low prevalence of HIV and syphilis. This highlights the importance of improving knowledge and awareness of HIV and syphilis infection among heterosexual STD clinic attendees on increasing the acceptance of PITC services.…”
Section: Discussioncontrasting
confidence: 88%
“…Secondly, even MSM who are willing to be tested often need to travel to other cities for testing in order to avoid social stigma [ 29 ]. Thirdly, younger MSM are less likely to have been tested for HIV, potentially due to their fear of HIV testing in healthcare settings [ 30 ], in our study about 54.4% of the participants were 25 years old or younger. Lastly, the geographical distribution of HIV testing sites is unbalanced in China [ 31 ].…”
Section: Discussionmentioning
confidence: 86%
“…Chinese government and some non-government organizations are investigating effective ways to reach young men, and mobile phone apps have been applied(1). However, an online video intervention promoting HIV testing among never-tested MSM in China (26) demonstrated that students had a lower testing rate compared with nonstudents at follow-up probably because of fear of testing in local healthcare institutions. Given the circumstance, peer education may be a complementary intervention.…”
Section: Discussionmentioning
confidence: 99%